Smart-Home Energy Management in the Context of Occupants' Activity (Informatica, 2014)
Energy consumption and occupants' comfort are key factors when evaluating smart-home environments.This paper focuses on occupants' comfort, which is affected by environmental factors (such as temperature,humidity, radiation of elements, and air movement), and occupant-related factors (such as occupants' levelof activity, clothing insulation). To satisfy a thermal comfort objective, energy is needed for heating andcooling, which affects energy consumption. This paper presents a proof-of-concept analysis of smart-homecontrol based on occupants' activity level in terms of human energy expenditure, and a trade-off analysis ofthe energy consumption versus thermal comfort when the activity level serves as an input into an intelligenthome energy management system.